The impact of alcohol‐based hand sanitiser and hand washing with soap and water on bacterial skin microbiota composition - Hilde Kristin Vindenes; Christine Drengenes; Hesham Amin; Randi Jacobsen Bertelsen (Wiley, 2023)
Abstract Background The use of alcohol‐based hand sanitiser (ABHS) and hand washing with soap and water increased during the COVID‐19 pandemic. Objectives We aimed to determine the immediate impact (<1 h) of hand hygiene measures on sampling and profiling of the bacterial skin microbiota. Methods Skin swab samples were collected from the dorsal hand and inner elbow from five volunteers before and after application of ABHS and before and after washing hands with soap and water. Bacterial composition was determined by MiSeq sequencing of the 16S rRNA gene. Results Bacterial composition on the hands was similar before and after application of hand sanitiser, with Streptococcus spp. (19.3%-18.4%), Propionibacterium spp. (11.7%-11.9%), Corynebacterium spp. (11.2%-11.3%) and Staphylococcus spp. (7.8%-7.4%) as the most prevalent genera. The relative abundance of bacteria changed after hand washing with soap and water for Streptococcus spp. (15.7%-9.2%), Propionibacterium spp. (12.1%-8.3%), Staphylococcus spp. (8.2%-5.2%) and Lactobacillus spp. (7.1%-2.9%). For alpha diversity, the number of amplicon sequence variants (ASVs) on the hand was lower after washing with soap and water: mean: 94.6 (SD: 12.3) versus before: 165.5 (SD: 12.7), p = 0.003. The ASV richness did not differ before and after hand sanitiser application (p = 0.2 for both hand and inner elbow). The Faith PD index was lower after washing with soap and water: mean: 6.6 (SD: 0.41) compared to before (9.5 [SD: 0.52]), p = 0.002, but no change was seen for application of hand sanitiser on hand (p = 0.3) or elbow (p = 0.5). Conclusions Skin microbiome diversity did not differ before and after hand sanitiser application but was lower after washing with soap and water, perhaps due to the mechanical removal of bacteria during hand washing. Both Gram‐negative and Gram‐positive bacteria were affected, with the largest impact on the Gram‐negative bacteria.